Profiling the 'Triple Crusade', c.1233-c.1241 - Reddish, H (2022)
During the late 1230s, the Mediterranean saw crusades launched across its full breadth. From Muslim Valencia in the West, through Frankish Greece to the Holy Land, the Mediterranean saw redemptive war waged by Latin Christendom upon its neighbours, whether those neighbours be Muslims, as in Iberian or the Levant, or schismatics and heretics, as in the Balkans. Despite the success all three of these campaigns attained, they are often overlooked by crusade historians, perhaps due to the comparatively small sizes of the Greek and Outremer campaigns. This thesis contends all three campaigns warrant further investigation, both in order to reveal more about the campaigns themselves, and as exemplars from which to ground points of general resonance about crusading history. In undertaking this investigation, this thesis takes a broad approach to the expeditions using a wide range of sources, both chronicle and documentary, both Eastern and Western.